2014
DOI: 10.1103/physrevapplied.2.044005
|View full text |Cite
|
Sign up to set email alerts
|

Composition Dependence of the Band Gap and Doping inCu2O-Based Alloys as Predicted by an Extension of the Dilute-Defect Model

Abstract: Tuning the opto-electronic properties through alloying is essential for semiconductor technology. Currently, mostly isovalent and isostructural alloys are used (e.g., group-IV and III-V), but a vast and unexplored space of novel functional materials is conceivable when considering more complex alloys by mixing aliovalent and heterostructural constituents. The real challenge lies in the quantitative property prediction for such complex alloys to guide their experimental exploration. We developed an approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…31 Upon Zn and Se substitution the band gap of the alloys shifts slightly to lower energies, as reported before. 17 This decrease of E g by À0.7x eV and À1.0y eV for Zn and Se, respectively, further aids the desired reduction of the effective absorption threshold of Cu 2 O (Fig. 1(c)).…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…31 Upon Zn and Se substitution the band gap of the alloys shifts slightly to lower energies, as reported before. 17 This decrease of E g by À0.7x eV and À1.0y eV for Zn and Se, respectively, further aids the desired reduction of the effective absorption threshold of Cu 2 O (Fig. 1(c)).…”
mentioning
confidence: 82%
“…16 In our recent computational study backed by preliminary experiments, we considered an alloying approach with aliovalent group IIA (Mg, Zn, Cd) and isovalent group VIA (S, Se) elements for tuning both the electrical and optical properties of Cu 2 O. 17 It was found that Zn Cu þ donors pair with V Cu À acceptors 18 to form 4-fold coordinated electrically neutral Zn 2Cu defect complexes that reduce the band gap of the alloy. Alloying with S/Se leads to binding of S O /Se O and V Cu þ , lowering the formation energy of V Cu þ and increasing the p-type doping, which is an unusual effect for isovalent alloying.…”
mentioning
confidence: 99%
See 3 more Smart Citations